Влияние редокс-потенциала среды на каталитическую активность НАД-зависимой гидрогеназы - Петров, Р.Р.; Уткин, И.Б.; Егоров, А.М.; Попов, В.О. (Биополимеры и клетка, 1987)
Исследовано влияние окислительно-восстановительного потенциала среды на каталитическую активность НАД-зависимой гидрогеназы водород-окисляющих бактерий Alcaligenes eutrophus Z1. Кофермент-зависимые реакции и реакция поглощения водорода в присутствии метилвиологена контролируются редокс-переходами с потенциалами полуволн —300 и —400 мВ соответственно. Обсуждается физиологическая роль редокс-регуляции каталитических свойств фермента. Досліджено вплив окиснювально-відновного потенціалу середовища на каталітичну активність НАД-залежної гідрогенази воденьокиснювальних бактерій Alcaligenes eutrophus Z1. Кофермент-залежні реакції і реакція поглинання водню за присутності метилвіологену контролюються редокс-переходами з потенціалами напівхвиль –300 і –400 мВ відповідно. Обговорюється фізіологічна роль редокс-регуляції каталітичних властивостей ферменту. The effect of redox potential of the medium on the catalytic properties of soluble hydrogenase from hydrogen-oxidizing bacteria Alcaligenes eutrophus Zl was studied. Two transitions on the catalytic activity of the enzyme vs redox potential profiles are observed: transitions with Em~—300 mV and Em~—400 mV control NAD(H)-dependent activities of enzyme and hydrogen uptake reaction with methyl viologen, respectively. These redox transitions may be accounted for by the model of the intramolecular electron transport chain of hydrogenase. A possible physiological role of the redox regulation of the hydrogenase catalytic activity is discussed. It is assumed that hydrogenase is regulated in vivo by the pool of nicotinamide adenine dinucleotides.